Intranasal Administration as a Route to Deliver Drugs to the Brain (Review) - N. N. Porfiryeva; I. I. Semina; R. I. Moustafine; V. V. Khutoryanskiy (Разработка и регистрация лекарственных средств, 2021)
Introduction. Intranasal drug delivery from nose-to-brain is one of the promising approaches for the treatment of brain diseases including neurodegenerative diseases, stroke, brain tumors, etc.Text. Delivery of drugs through the nose has a number of advantages, including the rapid onset of a pharmacological effect, the ability to bypass the blood-brain barrier, avoidance of some side effects and fast and non-invasive route of administration. However, the significant disadvantages of this route are rapid elimination of the drug from the surface of the mucosal membrane, poor penetration of the drug through the nasal mucosa, mucociliary clearance and effects of proteolytic enzymes. Currently, to overcome the above limitations, various approaches are used, including the development of delivery systems from nose-to-brain, which are mucoadhesive, mucus-penetrating and gel-forming systems that facilitate the retention or penetration of drugs through the mucosal membranes. At the same time, high-molecular weight compounds play a significant role in the design of these systems. In particular, mucoadhesive systems can be prepared from cationic and anionic polymers. Recent studies have also shown that interpolyelectrolyte complexes also exhibit mucoadhesive properties. An improvement in mucoadhesive properties of polymers can also be achieved by conjugating various functional groups such as thiols, maleimides, acrylates, methacrylates, catechols, etc. Mucus-penetrating systems can be prepared by PEGylation of nanoparticles, as well as functionalization with some poly(2-oxazolines), polyvinyl alcohol, etc. The mucus-penetrating ability of these polymers has been shown in other mucosal membranes in the body. Finally, increased penetration can be achieved by using mucolytic agents in combination with non-ionic surfactants. Another approach to increase the efficiency of drug delivery from nose-to-brain is the use of in situ gelling systems. Initially, this type of formulation exists as a solution; then a phase transition to gel is observed in response to chemical and physical effects. Depending on the external stimulation of the phase transition, thermo-, pH-, ion-reversible and other systems are known. These systems have shown effectiveness for delivery to the brain by intranasal administration.Conclusion. Effective intranasal delivery of drugs and therapeutic agents to the brain can be achieved by using mucoadhesive, mucus-penetrating, gelling systems and/or their combinations.